TiO2/rGO: Synthesis and application to cadmium and lead simultaneous determination by stripping voltammetry - Vũ , Ngọc Hoàng; Vũ , Thiên; Huỳnh, Ngọc Thiết; Nguyễn, Mậu Thành (Hue University Journal of Science: Natural Science, 2022)
In this paper, graphite powder was used to produce graphene oxide (GO), which was then reduced by ascorbic acid to gain reduced graphene oxide (rGO) with the Hummer method. Nano titanium dioxide (TiO2) is physically and chemically stable and used in numerous environmental applications. Reduced graphene oxide was modified with TiO2. The obtained TiO2/rGO was characterized by using X-ray diffraction, scanning electron microscopy and nitrogen adsorption/desorption isotherms. The synthesized material was applied to modify a glassy carbon electrode for the simultaneous determination of cadmium and lead with differential pulse anodic stripping voltammetry (DP-ASV). The method yielded a high sensitivity (0.329 ± 0.005 and 0.346 ± 0.004 μA/ppb for CdII and PbII), low detection limit (3.17 ppb and 2.42 ppb for CdII and PbII) and a good linear correlation between Ip and the metal concentration in the range of 6–80 ppb for both metals (R2 ≥ 0.998).